KEAKTIFAN OMK DALAM HIDUP MENGGEREJA DAN SUMBANGANNYA BAGI KATEKESE UMAT DI PAROKI KATEDRAL KELUARGA KUDUS BANJARMASIN DI MASA PANDEMI - Firdaus Piga Leo (Publisher STPKat, 2022)
Catholic youth are the heart of the Church, nation and state. The existence of a church will be determined by the young people in it. Likewise with the pastoral ministry of the Catholic Church, which requires young people to become drivers and motors to contribute talents and talents for the development of the people. Non-catechist religious teachers play an important role in proclaiming the Catholic faith through more concrete witness to life, education and teaching. The lack of involvement of young Catholics in the pastoral care of the Church is a big question that deserves to be investigated and resolved. This study focuses on young Catholics in Parish of Keluarga Kudus, Banjarmasin Cathedral. Young Catholics who are less active are also caused by many factors that must be studied one by one. This study aims to highlight the role and activity of young Catholics in the Holy Family Parish, Banjarmasin Cathedral and review their role in catechesis efforts among the people.